Graphene-advanced functional devices for integrated photonic platforms - Oleksiy Kovalchuk; Seungjae Gong; Hyowon Moon; Yong-Won Song (npj Nanophotonics)
Abstract Advances in optical data management require the integrated form factors of devices for high-speed, low-energy operation. Diversified nonlinear platforms benefit from graphene with broadband, ultrafast, and tunable dynamics, which are manageable by structure design. The operation also relies on fabrication approaches, including mechanical and chemical exfoliation, CVD, and atomic carbon spraying. We analyze and elucidate the device characteristics and provide their highlights depending on the structure and process factors.